Anticancer effect of Cenchrus ciliaris L - Esraa A. Alothman; Amani S Awaad; Norah A. Al-Qurayn; Haya F. Al-Kanhal; Reham M. El-Meligy; Yara M. Zain; Fatmah A. Alasmary; Saleh I. Alqasoumi (Saudi Pharmaceutical Journal, 2018)
Cenchrus ciliaris L total alcohol and successive extracts of both aerial and root parts were tested for their anticancer activities against lung (A-549), intestinal (CACO), colon (HCT-116), cervical (Hela), hepatocellular (HepG-2), and breast (MCF-7) (PC3) cell lines and compared with the standard drug vinblastine sulphate. The obtained results exhibited direct cytotoxic effect with variable inhibiting effect on the growth of the listed cell lines comparing to vinblastine sulphate as reference standard drug, these effects showed different IC50 ranged from 11.1 ± 0.3 to 267 ± µg/ml.All root extracts showed the best activities against most of the tested cell lines specially HepG-2 (Hepatocellular carcinoma) (9 ± 2.1 µg/ml) which was somewhat closely related to the effect of vinblastine sulphate (2.93 ± 0.3 µg/ml).The highest anticancer effect of Cenchrus ciliaris L aerial parts and root extracts were recorded on HepG-2 (Hepatocellular carcinoma) their IC50 were 12 ± 0.8 & 9 ± 2.1 respectively, CACO (colorectal carcinoma) their IC50 were 27.2 ± 1.6 & 20.5 ± 0.6 respectively, A-549 (Lung carcinoma) their IC50 were 14.5 ± 0.7& 11.1 ± 0.3 respectively which were better than the standard drug especially in case the anticancer effect on CACO (colorectal carcinoma) and A-549 (Lung carcinoma). Chloroform extracts of both aerial and roots achieved the best anticancer activities on all of the cell lines especially with colorectal (CACO) and Lung carcinoma (A-549). Cenchrus ciliaris could be a promising source of new chemical moieties used to target cancer cells. Keywords: Cenchrus ciliaris, Buffel grass, Poaceae, Cell lines, Anticancer effect, Phenolic compounds